E.U. paediatric MOG consortium consensus: Part 3 – Biomarkers of paediatric myelin oligodendrocyte glycoprotein antibody-associated disorders. (November 2020) - Armangue, Thaís; Capobianco, Marco; de Chalus, Aliénor; Laetitia, Giorgi; Deiva, Kumaran; Bruijstens, Arlette L.; Wendel, Eva-Maria; Lechner, Christian; Bartels, Frederik; Finke, Carsten; Breu, Markus; et al.
Abstract: A first episode of acquired demyelinating disorder (ADS) in children is a diagnostic challenge as different diseases can express similar clinical features. Recently, antibodies against myelin oligodendrocyte glycoprotein (MOG) have emerged as a new ADS biomarker, which clearly allow the identification of monophasic and relapsing ADS forms different from MS predominantly in children. Due to the novelty of this antibody there are still challenges and controversies about its pathogenicity and best technique to detect it. In this manuscript we will discuss the recommendations and caveats on MOG antibody assays, role in the pathogenesis, and additionally discuss the usefulness of other potential new biomarkers in MOG-antibody associated disorders (MOGAD). Highlights: Cell based assays with serum are the test of choice for MOG antibody testing. Serial testing of MOG antibodies can give information about risk of relapses. Recent data from animal models suggest that MOG antibodies are pathogenic. OCB have a high positive predictive value for the diagnosis of MS but not MOGAD. New biomarkers may help to monitor disease activity in MOGAD in the future.